Development of a simultaneously elementary analysis for clay minerals using EDXRF - Meor Yusoff, M. S.; Masliana, M.; Wilfred, P.; Parimala, Devi (Universiti Malaysia Perlis, 2010)
International Conference on X-Rays and Related Techniques in Research and Industry (ICXRI 2010) jointly organized by Universiti Malaysia Perlis (UniMAP) and X-Ray Application Malaysia Society (XAPP), 9th - 10th June 2010 at Aseania Resort Langkawi, Malaysia.